Early onset of deep sternal wound infection after cardiac surgery is associated with decreased survival: A propensity weighted analysis. Issue 12 (27th September 2021) - Elsayed, Ramsey S.; N. Carey, Joseph; Cohen, Robbin G.; Barr, Mark L.; Baker, Craig J.; Starnes, Vaughn A.; Bowdish, Michael E.
Abstract: Objectives: To compare outcomes after the development of early (≤30 days) versus delayed (>30 days) deep sternal wound infection (DSWI) after cardiac surgery. Methods: Between 2005 and 2016, 64 patients were treated surgically for DSWI following cardiac surgery. Thirty‐three developed early DSWI, while 31 developed late DSWI. The mean follow‐up was 34.1 ± 32.3 months. Results: Survival for the entire cohort at 1, 3, and 5 years was 93.9%, 85.1%, and 80.8%, respectively. DSWI diagnosed early and attempted medical management was strongly associated with overall mortality (hazard ratio [HR], 25.0 and 9.9; 95% confidence intervals [CIs], 1.18–52.8 and 1.28–76.5; p ‐value .04 and .04, respectively). Survival was 88.1%, 77.0%, 70.6% and 100%, 94.0% and 94.0% at 1, 3, and 5 years in the early and late DSWI groups, respectively (log‐rank = 0.074). Those diagnosed early were more likely to have a positive wound culture (odds ratio [OR], 0.06; 95% CI, 0.01–0.69; p  = .024) and diagnosed late were more likely to be female (OR, 8.75; 95% CI, 2.0–38.4; p  = .004) and require an urgent DSWI procedure (OR, 9.25; 95% CI, 1.86–45.9; p  = .007). Both early diagnosis of DSWI and initial attempted medial management were strongly associated with mortality (HR, 7.48; 95% CI, 1.38–40.4; p  = .019 and HR, 7.76; 95% CI, 1.67–35.9; p  = .009, respectively). Conclusions: Early aggressive surgical therapy for DSWI after cardiac surgery results in excellent outcomes. Those diagnosed with DSWI early and who have failed initial medical management have increased mortality.